Yeast strains from coconut toddy in Sri Lanka show high tolerance to inhibitors derived from the hydrolysis of lignocellulosic materials. Issue 1 (1st January 2019) - Ahangangoda Arachchige, Maduka Subodinee; Mizutani, Osamu; Toyama, Hirohide
Abstract: We previously isolated 18 Saccharomyces cerevisiae strains from coconut toddy in Sri Lanka. All the 18 strains (SLY-1 to SLY-18) could grow aerobically up to 18 mmol L −1 vanillin in yeast extract–peptone–dextrose (YPD) medium, and the SLY-10 strain showed the highest vanillin tolerance (up to 21 mmol L −1 ). Among these 18 strains, even in the presence of 24 mmol L −1 vanillin, five strains (SLY-3, SLY-4, SLY-8, SLY-9 and SLY-10) produced alcohol at 72 h in the range of 11.4–33.1 g L −1 and the SLY-10 strain showed highest alcohol production. The five strains showed the conversion of vanillin to vanillyl alcohol. They also tolerated other strong inhibitors: 4-hydroxybenzoic acid (24 mmol L −1 ), furfural (30 mmol L −1 ), 5-hydroxymethyl-2-furaldehyde (5-HMF, 36 mmol L −1 ) and acetic acid (75 mmol L −1 ). All these five strains showed no growth and no alcohol production when cultured in the medium with inhibitor mixture of 2.7 mmol L −1 vanillin, 30 mmol L −1 furfural, 30 mmol L −1 5-HMF, 75 mmol L −1 acetic acid and 75 mmol L −1 formic acid but showed significant growth and alcohol production of 16.2–32.7 g L −1 with inhibitor mixture of 30% concentration (0.81 mmol L −1 vanillin, 9 mmol L −1 furfural, 9 mmol L −1 5-HMF, 22.5 mmol L −1 acetic acid and 22.5 mmol L −1 formic acid). The four strains (SLY-3, SLY-4, SLY-8 and SLY-9) were shown to tolerate the inhibitor mixture to a similar extent and better than SLY-10, while SLY-10 was the best to vanillin alone.